Digital Information Resources and Business Education Delivery in Tertiary Institutions in Bayelsa State (British Journal of Multidisciplinary and Advanced Studies, 2024)
The study investigated the relationship between digital information resources and business education delivery in tertiary institutions in Bayelsa State. The study determined the relationship between the dimensions of digital information resources and business education delivery; thus, six objectives, research questions, and hypotheses guided the study. A correlational research design was used to carry out the study. The population of this study consisted of fifty-two (52) lecturers in business education from the three tertiary institutions in Bayelsa State. The census sampling technique was used in selecting the sample size of 52 business education lecturers for the study. The questionnaires for the study were developed based on the research objectives. The questionnaire was titled "Digital Information Resources and Business Education Delivery Questionnaire (DIRBEQ)." The questionnaire was subjected to face and content validity. The pilot-test approach was used to determine the reliability of the instrument. Cronbach’s alpha was also used to measure internal consistency. A reliability coefficient of 0.807 was obtained. This was considered sufficient for the study. The instrument was distributed by the researcher. Fifty-two copies of the questionnaire were filled out and collected. The research questions were answered using Pearson's product-moment correlation, while simple linear regression analysis and analysis of covariance were used to test the hypotheses at the 0.05 significance level. The study revealed that the extent of the relationship between e-book resources and business education delivery in tertiary institutions in Bayelsa State is weak, while the extent of the relationship between e-journal resources and business education delivery in tertiary institutions in Bayelsa State is very strong, among others. Furthermore, the study disclosed that there is a significant relationship between e-book resources and business education delivery in tertiary institutions in Bayelsa State and that there is a significant relationship between e-journal resources and business education delivery in tertiary institutions in Bayelsa State. The study concluded that digital information resources are an integral instructional delivery tool that can improve the quality of business education delivered to students at tertiary institutions in Bayelsa State. It was recommended that lecturers of tertiary institutions in Bayelsa State be trained in the use of e-book resources as well as the use of digital mediums in business education delivery, so that appropriate delivery of the lecture materials is ensured, and management of tertiary education in Bayelsa State should establish appropriate e-journal information management strategies that can foster lecturers' research skills, attitude, and competence for information literacy, effective e-journal use, and professional practices, among others.